Qualidade de Vida e Fatores Associados em Idosas Participantes de Grupos da Terceira Idade da Unicentro-Pr, 2019 - Bortolanza, Marciane Conti Zornita (2020)
Population aging is making great strides. The evolution of medical sciences, better conditions of access to health and resocialization of the elderly has changed the world scenario. Such factors reflected in changes in the system in order to develop actions to improve the possibilities of healthy an active aging. Objective: Analyzing the Quality of Life indicators in elderly women who participate in two senior groups linked to Unicentro University, according to sociodemographic, behavioral and health-related characteristics. Methods: Cross-sectional and quantitative study. Developed with two groups of elderly people participating in the Open University for the Elderly (UATI/UNATI) at the Universidade Estadual do Cantro Oeste (UNICENTRO). In total of 70 elderly woman participed in the study, age 60 years or older. Descriptive statistics of the variables were performed and, to identify the factors associated with Quality of Life, the Linear Regression models were constructed, in univariate and multivariate models, which were estimated by points and intervals with 95% confidence. Variables for which p <0.25 (Wald test) were candidates to the multivariate models. In the final multivariate models, the variables with p values <0.05 remained. The group were predominantly composed of women in the first age groups (59 to 79 years old) who were living without a partner (62.96% UATI and 67.44% UNATI), and who fit different income and education tertiles, whereas in the Guarapuava group, women with high levels of income and education were predominant. Results: The elderly participants in the UNATI group demonstrated greater contentment related to the quality of life relating to the social relations domain (88.18%) and greater discontentment with the psychological domain (84.40%). The Uatianas demonstrated higher contentment with the environmental domain (87.04%) and lower contentment with the physical domain (82.28%). Regarding to Self-rate quality of life (87.21%) of women in the UNATI group were pleased, while in the UATI group (78.70%) reported contentment with their quality of life. Among the highlighted variables that remained associated with the final outcome, quality of life can be mentioned self-reported health, marital status and sarcopenia.Conclusion: The main factors that negatively influenced the Quality of Life reported in the UNATI group are the poor ease of learning and memorizing new things, as well as difficulty concentrating, while the complaint of the UATI group reports some kind of pain or discomfort.